2021
DOI: 10.3390/s21051875
|View full text |Cite
|
Sign up to set email alerts
|

RF-Based Moisture Content Determination in Rice Using Machine Learning Techniques

Abstract: Seasonal crops require reliable storage conditions to protect the yield once harvested. For long term storage, controlling the moisture content level in grains is challenging because existing moisture measuring techniques are time-consuming and laborious as measurements are carried out manually. The measurements are carried out using a sample and moisture may be unevenly distributed inside the silo/bin. Numerous studies have been conducted to measure the moisture content in grains utilising dielectric properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…The recommended moisture level for rice storage to maintain optimum quality ranges from 14% to 16% [ 18 ]. In this research, the moisture content of rice samples was increased using the moistening method used in the previous research [ 19 , 20 , 21 , 22 ]. The samples with different moisture contents can be obtained by adding a predetermined amount of distilled water, , as calculated from Equation (2).…”
Section: Methodsmentioning
confidence: 99%
“…The recommended moisture level for rice storage to maintain optimum quality ranges from 14% to 16% [ 18 ]. In this research, the moisture content of rice samples was increased using the moistening method used in the previous research [ 19 , 20 , 21 , 22 ]. The samples with different moisture contents can be obtained by adding a predetermined amount of distilled water, , as calculated from Equation (2).…”
Section: Methodsmentioning
confidence: 99%
“…The model must find the k observations with the closest x i to x and average their responses [ 41 ]. Based on the distance, the analysed sample is classified in the class to which the majority of the neighbours belong [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The model must find the k observations with the closest x i to x and average their responses [41]. Based on the distance, the analysed sample is classified in the class to which the majority of the neighbours belong [42]. This classifier has shown important results in the classification of the land cover from data extracted from Sentinel 2 satellite images, reaching classification accuracies of 94% [43].…”
Section: K-nearest Neighboursmentioning
confidence: 99%
“…RFID was only used for position and tracking while the drone was used for counting animals using cameras. A study reported using RFID and wireless technology to predict the moisture content of rice [18]. Both the Received Signal Strength Indicator (RSSI) from the two wireless transceivers were used for predicting the moisture content in rice using Artificial Neural Network.…”
Section: Introductionmentioning
confidence: 99%